The Rethoric of Space Representation: From Drawing Heritage to Visual Computing - Michela Rossi; Luca Armellino (img journal, 2023)
Digital technology connects people in digital space focusing the attention on images, which create and introduce you into artificial spaces. The development of digital technology offers the possibility of living immersive experiences in suitable activities to improve real skills in digital ‘room’. That means the possibility of exploring otherwise impossible space, opening to new applications of visual arts. Digital reality explores imaginary worlds through senses, first of all the sight. Hybrid reality becomes actual through visual images. Because of that the imaging requires first of all the management of visual space. Perspective makes believable the space visualization, and the drawing tradition becomes the main reference to the design of suitable space, as well in the rhetoric of impossible world. The architectural drawing enhances the perspective by light and shadow, more than color. Besides the unreal architecture, the graphic art shows interesting representations of abstract mathematical spaces, referred to the concepts of Not Euclidean Geometry. Some considerations open a further research comparing the drawing tradition with last trends in contemporary imagery, starting with Utopia’s imaginary architecture. Today images confirm the role of the perspective, thus the relationship between the eye and the room.